Prevalence and correlates of parkinson’s disease among elderly patients attending Neurology Clinic at Serdang Hospital in 2016 - Minhat Halimatus Sakdiah,; Liyana Najwa Inche Mat,; Abdul Syafiq A. Radzis,; Ng, Yiet Fai; Nur Syazwany Nasir Khan, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction Parkinson’s disease (PD) is the second most common neurodegenerative disease after Alzheimer’s disease (AD) and the most frequent sub-cortical degenerative disease, characterized by universal progressive disorder of the nervous system that affects movement. This cross sectional study aimed to determine the prevalence and correlates of PD among elderly attending the neurology clinic in Serdang Hospital. Methods A total of 150 records of patients attended the clinic from January to December 2016 were randomly selected. Data was collected using a proforma form seeking information related to age, gender, race, locality, and presence of comorbidity particularly diabetes mellitus. The data was analysed using the Statistical Package for Social Science (IBM SPSS) version 22.0. Results The prevalence of PD among the elderly involved in the study was 34%. Majority of the respondents were aged 60 to 70 years old (54.7%), male (53.3%), Chinese (56.7%), from urban locality (93.0%) and were not diabetic (69.3%). The inferential statistics showed no significant association between all the factors with PD. However, the associations between age and diabetes mellitus with PD were almost significant with p values of 0.07 and 0.08 respectively. Conclusions Overall, the prevalence of PD among elderly who attended the neurology clinic in year 2016 was less than half with none of the factors under study were significantly associated with PD. However with bigger sample size, possible significant association may be obtained between age and diabetes mellitus.